PENGETAHUAN IBU TENTANG PENYAKIT YANG DAPAT DICEGAH DENGAN IMUNISASI PADA BAYI - Husna Sari; Erlina Hayati (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
Immunization is a program that deliberately introduces weak antigens to stimulate antibodies out so that the body can be resistant to certain diseases. Diseases that can be prevented by immunization are tuberculosis, tetanus, diphtheria, pertussis, polio, measles, and hepatitis B. This disease can cause death, morbidity, and disability, even if not treated optimally can be contagious and cause extraordinary events. The purpose of this study is to describe how the mother's Knowledge about diseases that can be prevented by immunization in infants. The design in this study was descriptive, using primary data obtained directly from respondents through a questionnaire. The population in this study were all mothers who had babies in the Veterans Region of Medan Estate Village Percut Sei Tuan Medan District by using a total sampling technique of 20 respondents. Data processing is done through the process of editing, coding, tabulating. The results showed that knowledge of mothers about diseases that can be prevented by immunization in dominant infants with sufficient knowledge was 14 people (70%). So it can be concluded that the mother's knowledge about diseases that can be prevented by immunization in infants is categorized as sufficient. It is hoped that with increasing knowledge, mothers will be more active in bringing their babies to the public health for immunization. Midwives and cadres are also expected to be more active in disseminating health information about diseases that can be prevented by immunization to residents, especially to mothers who have babies.